2022
DOI: 10.2478/jvetres-2022-0042
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of Fascioloides magna (Bassi, 1875) in the wild cervid population in the Lower Silesian Wilderness – epidemiological and pathological aspects

Abstract: Introduction Fascioloides magna is a parasite of high veterinary importance due to its pathogenicity for wild and domestic ruminants. The aim of our study was to describe the presence of trematode infection in the red deer population in the Lower Silesian Wilderness, one of the established fascioloidosis foci in Central Europe, and to assess the overall prevalence of F. magna in the studied area. In order to achieve this, a coprological study of different cervid species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Cervids originating from central Europe showed severe hepatic lesions in response to F. magna infection, as well as liver hypertrophy, and large areas of the liver surface on the diaphragm side were covered with fibrin [ 59 ]. The results of the present study revealed the presence of one to six pseudocysts that contained a hemorrhagic liquid and harbored 4–39 adult flukes with a length of 3.8–8.2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Cervids originating from central Europe showed severe hepatic lesions in response to F. magna infection, as well as liver hypertrophy, and large areas of the liver surface on the diaphragm side were covered with fibrin [ 59 ]. The results of the present study revealed the presence of one to six pseudocysts that contained a hemorrhagic liquid and harbored 4–39 adult flukes with a length of 3.8–8.2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Our results supported a previous finding. The F. magna could be able to reach sexual maturity and produce fertile eggs in roe deer [ 6 ], whose species is currently known as the aberrant host. On the other hand, we confirmed that the parasite has the potential for selfing (self-fertilisation), which was previously observed in its relatives, within the order Echinostomida [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The signs of this possible co-evolutionary process can be detected. Within its older European habitats, faecal egg shedding is also confirmed [ 6 ], while it is lacking in newly invaded areas [ 5 ]. Pseudocyst formation in roe deer, as the sign of an advanced stage of infection, has already been found in all European F. magna habitats [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations